Zatoichi and the Fugitives Based on a Short Story by Kan Shimozawa - Yasuda, Kimiyoshi; Miyagawa, Kazuo; Katsu, Shintaro; Mikimoto, Kayo; Machida, Kyôsuke (Zatoichi: The Blind Swordsman Collection, 2019)
The wandering swordsman finds himself in a small village that serves as hideout for a band of fugitives who control the town officials and enforce brutal slave labor in the local silk mill. This lean and mean entry is packed with coldhearted villainy and rough justice, but it finds its heart in the great Takashi Shimura (Ikiru), who plays a kindly country doctor caught up in a violent world. [www.criterion.com]